Оценка остаточного члена в центральной предельной теореме для r-независимых случайных величин - Шарахметов, Ш. (Український математичний журнал, 1993)
We suggest a method for the investigation ofr-independent random variables by using multiplicative systems. An estimate of the remainder term in the central limit theorem forr-independent random variables is obtained.